Thai Loanwords in Bangkok Chaozhou: Types of Loans and Lexical Variation by Age Groups - Chawla, Chanyaporn (Journal of Sinology (วารสารจีนวิทยา), 2015)
The objective of this research is to study Thai loanwords in Bangkok Chaozhou, focusing on types of loanwords and to analyze the variation of those words, according to ages of Chaozhou speakers. The data were collected from literature, short stories, Chinese newspapers printed in Thailand, and the researcher herself who is a bilingual Thai-Chaozhou. The result reveals that most of the Thai loanwords in Bangkok Chaozhou are loanwords (outright transfer), not loan translations nor loan blends, and most of them are nouns, verbs, and classifiers, respectively. A large number of loanwords are relevant to food, occupation and forms of addressing others. As for the variation of the words according to ages of Chaozhou speakers, this paper reveals that the speakers’ age has some influence on the variation in word choice. The first generation group tends to use Chaozhou words, loan translations or loan blends more frequently than the second generation group. This is because the second group possesses a limited Chaozhou vocabulary and has Thai language influence. Moreover, the first generation group also reported that some words can use either Chaozhou or Thai loanwords interchangeably. It is likely that in the future these Chaozhou words will disappear and be replaced by the Thai ones.